The Use of Microstrategies in Students' Translation: A Study on Classroom Translation Process and Product - Raden Arief Nugroho (PRASASTI: Journal of Linguistics, 2013)
This paper discusses about the microstrategies of translation used by undergraduate students of English studies of Dian Nuswantoro University. Accordingly, these microstrategies are proposed by Schjoldager (2008). The use of Schjoldager’s microstrategies is based on three reasons, they are: 1) these microstrategies are more specific and thorough and also outnumber the other translation strategies; 2) the use of translation microstrategies fits with students’ status as non professional translators; 3) they can show the degree of creativity applied in a translation work. In order to get the data, a translation task was applied in this study. Therefore, both translation process and products became crucial elements in this study. As a result, six microstrategies are applied by the students. Surprisingly, students who achieve the GPA below 2.75 are more creative than students who achieve 2.75 GPA or above. Keywords: Microstrategies, creativity, translation strategies